A minimal biochemical route towards de novo formation of synthetic phospholipid membranes - Ahanjit Bhattacharya (Nature Portfolio, 2019)
The origin of phospholipids, the primary constituents of cell membranes, is uncertain. Here, the authors develop an in vitro system to synthesize phospholipid molecules from water-soluble single-chain amphiphilic precursors via a reaction catalysed by the mycobacterial ligase FadD10.